2007
DOI: 10.1007/s11145-006-9036-8
|View full text |Cite
|
Sign up to set email alerts
|

Rebounding activation caused by lexical homophony in the processing of Japanese two-kanji compound words

Abstract: The present study investigated the effects of lexical homophony on the processing of Japanese two-kanji compound words. Experiment 1 showed that participants took longer to perform lexical decisions for words with a high degree of lexical homophony than those with no homophony. Interestingly, the same inhibitory trend was found in the naming task of Experiment 2. Participants took longer to name words with a high degree of lexical homophony than those with no homophony. The consistency of an inhibitory effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
4
21
2
Order By: Relevance
“…1 Thus, just like the processing advantage observed in the Chinese studies, a homophone advantage might be expected for kanji words. In contrast to this expectation, however, Tamaoka (2007) reported a significant homophone disadvantage in his lexical decision and naming tasks with kanji words.…”
Section: Japanese Kanjicontrasting
confidence: 68%
See 1 more Smart Citation
“…1 Thus, just like the processing advantage observed in the Chinese studies, a homophone advantage might be expected for kanji words. In contrast to this expectation, however, Tamaoka (2007) reported a significant homophone disadvantage in his lexical decision and naming tasks with kanji words.…”
Section: Japanese Kanjicontrasting
confidence: 68%
“…However, another possibility is that there was a confound in Tamaoka's (2007) stimuli. As is described below, Tamaoka's (2007) homophones and nonhomophones were not well matched in terms of familiarity ratings; hence, it is possible that the effect observed with these stimuli may actually be a familiarity effect rather than a homophone effect.…”
Section: Japanese Kanjimentioning
confidence: 99%
“…Our findings of null effect, or at best a trend of advantage regarding homophone processing in Japanese, weakly echoed the reported advantage in processing multi-mate homophones (Hino et al, 2013), but challenged the findings of a disadvantage in visual processing (Tamaoka, 2007;Mizuno & Matsui, 2016). Similar to the situation in Mandarin, the existing inconsistencies regarding homophone effects in visual word processing prevents us from any conclusive argument within Japanese.…”
Section: Figure 2 Effect Of Each Additional Meaning In Japanese Mansupporting
confidence: 47%
“…Inconsistencies between findings on homophone processing have mostly come from studies that examined homophone effects in Japanese and Mandarin. For example, while Tamaoka (2007) reported a homophone disadvantage in Japanese similar to that found in English within both visual lexical decision and word naming tasks, Hino and colleagues (2013) reported that such a disadvantage was limited to mono-mate homophones, and for homophones with more than one mate, participants, on the contrary, responded faster than they did for mono-meanings words. However, a recent study by Mizuno and Matsui (2016) challenged the findings by Hino and colleagues, showing that homophones in general had longer response latencies than monomeaning words, and multi-mate homophones had even longer latencies than single-mate homophones.…”
Section: Homophone Processing In An Auditory Lexical Decision Taskmentioning
confidence: 90%
“…For example, homophone effects have been observed for Kanji words in lexical decision studies (Hino, Kusunose, Lupker, & Jared, 2013;Tamaoka, 2007) and in category decision studies (Morita & Saito, 2007;Sakuma, Sasanuma, Tatsumi, & Masaki, 1998;Wydell, Patterson, & Humphreys, 1993). The evidence is mixed regarding whether phonological priming occurs when both primes and targets are in Kanji.…”
Section: Japanese Kanjimentioning
confidence: 99%